Quality of life, anxiety and depression in Dentistry students in the COVID-19 pandemic and related (Research, Society and Development, 2021)
Objective: To assess the impact of social isolation on the quality of life of dental students. Methodology: used Google forms addressing sociodemographic aspects; assessment of quality of life (WHOQOL-brief) and scale of anxiety, depression and stress (EADS-21). Data analyzed with Mann Whitney and Kruskal-Wallis tests; and Pearson's Correlation to verify the relationship between WHOQOL-brief and EADS-21 scores (α = 0.05). Results and Discussion: 249 students participated, 80.3% being women, between 18 and 23 years old (70.7%), who were in capitals (57.8%), with relatives or relatives (95.2%). Observe norms of stress (46.2%), anxiety (39.4%) and depression (41.8%). There was prejudiced us physical (46.42 ± 13.12) and psychological (62.50 ± 18.75) domains of quality of life. Young women and students will experience significantly higher levels of stress, anxiety and depression. Women were most harmed us physical, psychological and environmental domains; Younger students, no psychological domain. It was observed that a significant non-physical domain prejudice was those who estimate internal cities in our psychological and social domain, those who estimate alone. There is a positive correlation between the various stresses, anxieties and depression; There is also a negative correlation between these various domains of quality of life, being higher between depression and the psychological domain. Conclusion: You will show that younger students, of feminine sex, that they estimate their inner situations and inner cities, they will show higher quality of life.